Improving Self-Help E-Therapy for Depression and Anxiety Among Sexual Minorities: An Analysis of Focus Groups With Lesbians and Gay Men - Rozbroj, Tomas; Lyons, Anthony; Pitts, Marian; Mitchell, Anne; Christensen, Helen (JMIR Publications, 2015)
BackgroundE-therapies for depression and anxiety rarely account for lesbian and gay users. This is despite lesbians and gay men being at heightened risk of mood disorders and likely to benefit from having access to tailored self-help resources. ObjectiveWe sought to determine how e-therapies for depression and anxiety could be improved to address the therapeutic needs of lesbians and gay men. MethodsWe conducted eight focus groups with lesbians and gay men aged 18 years and older. Focus groups were presented with key modules from the popular e-therapy "MoodGYM". They were asked to evaluate the inclusiveness and relevance of these modules for lesbians and gay men and to think about ways that e-therapies in general could be modified. The focus groups were analyzed qualitatively using a thematic analysis approach to identify major themes. ResultsThe focus groups indicated that some but not all aspects of MoodGYM were suitable, and suggested ways of improving e-therapies for lesbian and gay users. Suggestions included avoiding language or examples that assumed or implied users were heterosexual, improving inclusiveness by representing non-heterosexual relationships, providing referrals to specialized support services and addressing stigma-related stress, such as "coming out" and experiences of discrimination and harassment. Focus group participants suggested that dedicated e-therapies for lesbians and gay men should be developed or general e-therapies be made more inclusive by using adaptive logic to deliver content appropriate for a user's sexual identity. ConclusionsFindings from this study offer in-depth guidance for developing e-therapies that more effectively address mental health problems among lesbians and gay men.